Energy Management in Manufacturing SMEs in East Midlands: Practices and Challenges - a Deductive Approach - Pinon, Claudia (2017)
This dissertation empirically researches the factors that impedes and drives the energy efficiency practices implementation by manufacturing SMEs in East Midlands. The analysis is based on data gathered from web-based surveys from associated and non-associated SMEs. Overall, the findings corroborate the idea that policy makers need flexibility to adapt energy systems to SMEs different situations if it is pursed to achieve a real development in energy efficiency field. In case of East Midlands manufacturing SMEs, economical barriers and the perception of insufficient incentives seems to hamper energy efficiency development in firms. Hence, investment subsides combined with strong awareness campaigns may significantly decrease financial constraints.